(untitled) (International Journal of Nursing Education, 2021)
Background: This contemporary technological era is witnessing internet addiction as an emerging global concern and burden on mental health and society. It is a multidimensional phenomenon that affects an individual physically, psychologically, and socially. Objective: The objective of this review was to describe internet addiction and examine its affecting factors among undergraduate university students. Methods: This integrative review was conducted to examine the affecting factors related to internet addiction among university students using PRISMA guidelines.A systematic search was conducted using Academic Search Complete (EBSCO), PubMed, MEDLINE, APA PsycArticles, CINAHL, SCOPUS, google scholar, ScienceDirect published in the English language between the year January 2011 to January 2021. Results: A total of seventeenarticles were retrieved and their results were synthesized. The findings revealed three common measurement tools namely Internet Addiction Test (IAT), Young’s Diagnostic Questionnaire (YDQ), and Chen’s Internet Addiction Scale (CIAS). Two factors were found related to internet addiction, internal factors that include demographic factors and psychological factors and external factors like external financial funding, and internet accessibility in college. Conclusion:As internet addiction leads to many psychiatric comorbidities, identification of the factors contributing to this phenomenon needs more attention and careful consideration for prevention strategies.